Mechanical Characteristics of Prestressed Concrete Cylinder Pipe Strengthened by EPS and CFRP Liner - Zhai, Kejie; Dang, Mingzhe; Zhang, Yi; Chen, Qiang; Li, Bin; Wang, Niannian; Du, Xueming; Cui, Penglu (Salehan Institute of Higher Education, 2025)
Prestressed concrete cylinder pipe (PCCP) has been applied in many large-scale hydraulic engineering projects around the world. And the prestressed wire breakage is the most common form of PCCP damage. Traditional carbon fiber reinforced polymer (CFRP) liner techniques fail to fully exploit the tensile performance of CFRP. Therefore, the method of using EPS cushion and CFRP liner to strengthen the PCCP with broken wire is proposed in this study. To clarify the effect of the proposed method, a finite element three-dimensional model is established and validated using experimental data. Subsequently, the effects of EPS thickness, CFRP thickness, and wire breakage ratio on the stress-strain response of the PCCP are analyzed. Based on different failure modes of the pipe, the influence of EPS and CFRP thickness on the internal pressure bearing capacity is discussed. The study reveals that the synergistic action of the EPS cushion can effectively enhance the internal pressure bearing capacity of the PCCP. As the thickness of EPS cushion and CFRP increases, the bearing capacity almost linearly increases. Under the influence of internal pressure, visible cracks first appear in the concrete core, followed by yielding of the steel cylinder, and finally the steel wire stress reaches its ultimate strength.